Determinants of outpatient service use among Orang Asli in Malaysia using Andersen’s Behavioural Model - Iqbal Ab Rahim; Nur Elina Abdul Mutalib; Sivaraj Raman; Devi Shantini Rata Mohan; Awatef Amer Nordin; Suhana Jawahir; Sarah Nurain Mohd Noh; Jabrullah Ab Hamid; Hamizatul Akmal Abd Hamid; Tania Gayle Robert Lourdes; Thamil Arasu Saminathan; Mohd Hatta Abdul Mutalip; et al. (PLoS ONE, 2026)
Background Indigenous populations, including the Orang Asli in Malaysia, experience persistent health disparities due to historical, socioeconomic, geographic, and cultural barriers. Despite government initiatives to improve access, significant gaps remain, and limited nationwide data hinder policy development. This study examines the prevalence and determinants of outpatient healthcare utilisation among the Orang Asli. Methods This study utilised data from the Orang Asli Health Survey, a nationwide cross-sectional survey of Orang Asli communities in Peninsular Malaysia, with 89.8% response rate. Andersen’s Behavioural Model was applied in the analysis to assess the predisposing, enabling, and health need factors influencing outpatient healthcare use among the adult (aged 18 and over) population. Weighted descriptive statistics and logistic regression were used to examine outpatient healthcare utilisation and its determinants. Analyses were performed in STATA 18. Results The overall prevalence of outpatient service utilisation in the past 12 months was 17.9%. Higher utilisation was observed among females, urban residents, and the Senoi and Negrito tribes. Determinants of outpatient use included female (adjusted odds ratio [aOR]: 1.64, 95% CI: 1.31–2.06), urban locality (aOR: 2.39, 95% CI: 1.15–4.96), Senoi (aOR 2.66; 95% CI: 1.52–4.64) and Negrito (aOR: 3.91, 95% CI: 2.01–7.60) tribes, unemployment (aOR: 1.27, 95% CI: 1.11–1.46), recent acute health problems (aOR: 2.17, 95% CI: 1.68–2.81), fair to very poor self-rated health (aOR: 2.30, 95% CI: 1.39–3.79), and presence of one (aOR: 2.90, 95% CI: 2.00–4.21) or two or more non-communicable diseases (NCD) (aOR: 4.63, 95% CI: 2.89–7.41). Interaction effects indicated lower outpatient use among Senoi and Negrito adults with poor self-rated health compared to other groups. Conclusion Outpatient healthcare utilisation among Orang Asli adults was driven by gender, tribe, health needs, and NCDs. Improved access requires needs-based sensitive interventions and existing services optimisation. Follow-up studies are warranted to explore the underlying cultural behavioural aspects.